Amino acid sequence of the N-terminal 139 residues of light chain derived from a homogeneous rabbit antibody - Jaton, Jean-Claude (1974)
The amino acid sequence of the N-terminal 139 residues of the L (light) chain derived from a homogeneous rabbit antibody (designated BS-1) to type III pneumococci was determined. A combination of methods involving tryptic cleavage restricted to the 2 arginine residues of the molecule and mild acid hydrolysis of a labile peptide bond between the V (variable) and C (constant) regions of the L chain (Fraser et al., 1972) allowed the isolation of two large peptides comprising the entire V region (residues 1–109); these peptides were suitable for automated Edman degradation. The complete sequence analysis of the V region was carried out with only 4μmol of L chain. This material was homogeneous, although minor variant sequences, if present at the 10% value, would not have been detected. The L chain contains 3 intrachain disulphide bridges, whose pairing was established by diagonal electrophoresis: there is one V-region bridge between positions 23 and 88 and one C-region bridge between positions 134 and 194; the third one connects V and C domains between positions 80 and 171. When compared with the basic sequence of human κ chains, rabbit L chain BS-1 appears to be more similar to the V(KI) prototype sequence than to V(KII) or V(KIII) sequences, where V(KI), V(KII) and V(KIII) represent subgroups I, II and III respectively of V regions of κ light chains. The V regions of rabbit heavy and light chains are homologous to each other. The presence of two clusters of 3 glycine residues in positions 94–96 and 99–101 respectively is remarkable. Residues 94–96 may be related to antibody complementarity whereas residues 99–101 function probably as a pivot permitting the combining region of the L chain to make optimal contact with the antigenic determinant (Wu & Kabat, 1970).